1978
DOI: 10.1111/j.1744-313x.1978.tb00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Structural Variation and Linkage Relationships of C7

Abstract: SUMMARY Three structural forms of C7 have been distinguished by isoelectric focusing. They are the products of three co‐dominantly expressed alleles at an autosomal locus. The C7 locus is close to that for C6, but is not close to the HLA complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 18 publications
5
57
1
Order By: Relevance
“…Previous studies on C7 polymorphism suggested that C7 3 might be a 'hypomorphic' variant (Hobart et al, 1978;Nishimukai and Tamaki 1986;Washio et al, 1986). Our present investigation demonstrates that both the immunochemical and functional C7 levels for C7 3-1 are lower than those for the other common phenotypes.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…Previous studies on C7 polymorphism suggested that C7 3 might be a 'hypomorphic' variant (Hobart et al, 1978;Nishimukai and Tamaki 1986;Washio et al, 1986). Our present investigation demonstrates that both the immunochemical and functional C7 levels for C7 3-1 are lower than those for the other common phenotypes.…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, two rare variants have been reported, one in a Chinese individual (Zeng et al, 1986), and the other in a Japanese individual (Washio et al, 1986). It is interesting that both C6 (the sixth component of complement) and C7, which are tightly linked each other (Hobart et al, 1978;Tokunaga et al, 1986), show a higher degree of polymorphisms in East Asian populations than in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The close linkage between C6 and C7 loci has been confirmed (Hobart et al, 1978;Tokunaga et al, 1986). A genetic study of structural variants of the seventh component of human complement (C7) was first carried out by Hobart et al (1978), using polyacrylamide gel isoelectric focusing followed by functional detection.…”
Section: Introductionmentioning
confidence: 79%